Literasi Digital : Pemanfaatan dan Penggunaan E-Library Menggunakan Software SLiMS" di Desa Denai Lama, Pantai Labu-Deli Serdang - Zufria, Ilka; Hasugian, Abdul Halim; Suhardi; Hasibuan, Muhammad Siddik; Lubis, Aidil Halim; Armansyah (Jurnal Pengabdian Masyarakat, 2022)
Information technology has developed very rapidly and covers various fields. The field of education is one area that is influenced by information technology. Both in the formal learning process at school and non-formal in the form of training outside of school. The form of participation from universities, especially the Computer Science study program, FST UIN North Sumatra Medan, in this community service activity is to provide skills training in the field of information technology in the form of digital literacy and the use of SLiMS software to the Circle Community Reading Park (TBM), Denai Lama Village, Labu Beach. Deli Serdang, North Sumatra which was held with the theme "Digital Literacy: Utilization and Use of E-Library Using SLiMS Software".